Paleogene taphoflora of the Entre-Córregos Formation (Aiuruoca Basin): foliar architecture and paleoclima - Amanda Hoelzel; Mary Elizabeth Cerruti Bernardes-de-Oliveira; Maria Cristina de Castro-Fernandes (Geologia USP. Série Científica, 2013)
The present study aims to analyze the leaf architecture of the Entre-Crregos Formation plant fossils, from the municipality of Aiuruoca, State of Minas Gerais. Based on these foliar architectural features and their meanings as climatic adaptation, the work shows that during the Middle Paleogene (Late Eocene-Early Oligocene), this region had high temperatures and wet weather, and was included into a tropical everwet biome going on to a subtropical summerwet.